Benthic Structure and Pelagic Food Sources Determine Post-settlement Snapper (Chrysophrys auratus) Abundance - Lohrer, Andrew Martin; McCartain, Lisa D.; Buckthought, Dane; MacDonald, Iain; Parsons, Darren M. (Frontiers in Marine Science, 2018)
Nursery habitats provide increased survival and growth and are a crucial early life-stage component for many fish and invertebrate populations. The biogenic structures that provide this nursery function, however, are increasingly degraded. Therefore, any effort to conserve, restore or replace habitat with artificial structure should be guided by an understanding of the value provided by that nursery habitat. Here we experimentally manipulated structure across a number of sites by inserting pinnind bivalve mimics into the seabed and deploying video cameras to observe the response of post–settlement stage snapper, Chrysophrys auratus (Forster in Bloch and Schneider 1801). We also collected a range of environmental variables across these sites to determine the relative importance to snapper of benthic vs. pelagic productivity. While the abundance of snapper was low, our results demonstrated a strong association to structure relative to control plots. The environmental variable with the highest correlation to snapper abundance was the abundance of zooplankton eaten by snapper. This result was well supported by the dominance of zooplankton over small benthic invertebrates in snapper gut contents, and the weak influence of benthic infauna in our regression models. These regressions also demonstrated that when combined with zooplankton abundance, turbidity had a negative relationship to snapper abundance. This highlights the importance of relatively clear water in estuaries, which allows post–settlement snapper to more efficiently consume the zooplankton that are present in the water column. The third component that post–settlement snapper require is of course the presence of benthic structure. While benthic habitat structure was the strongest factor affecting juvenile snapper abundance, we did not find any correlations to suggest that this importance was related to energetic sheltering and access to locations with high food flux.